1952
DOI: 10.5962/bhl.title.5237
|View full text |Cite
|
Sign up to set email alerts
|

A classification of the Conularida

Abstract: The seventeen genera of the Conulariidae are grouped into three new subfamilies. Six new genera and two new species are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 2 publications
(2 reference statements)
0
24
1
1
Order By: Relevance
“…However, the underlying mechanism of the coaxing effect has not been elucidated yet. It has been reported that the coaxing effect appears when work hardening 11) or strain-age hardening of carbon 12,13) are significant during fatigue. The latter factor likely plays an important role in the appearance of the coaxing effect in ferritic steels.…”
Section: Intrinsic Factors That Trigger the Coaxing Effect In Binary mentioning
confidence: 99%
“…However, the underlying mechanism of the coaxing effect has not been elucidated yet. It has been reported that the coaxing effect appears when work hardening 11) or strain-age hardening of carbon 12,13) are significant during fatigue. The latter factor likely plays an important role in the appearance of the coaxing effect in ferritic steels.…”
Section: Intrinsic Factors That Trigger the Coaxing Effect In Binary mentioning
confidence: 99%
“…[15][16][17] More specifically, chemical composition affecting microstructure and strength plays a key role on the microstructurally-small fatigue crack propagation behavior. In particular, carbon is the most important element in fatigue of steels.…”
Section: )mentioning
confidence: 99%
“…Debido a que algunos caracteres cuantitativos de los conuláridos pueden verse afectados por factores tafonómicos (Leme et al, 2004), se atendieron las recomendaciones de Rodrigues (2002) y Leme (2002), realizándose descripciones con base en el mayor número posible de ejemplares que en su mayoría están bien conservados y completos o casi completos. Se sigue la clasifi cación de Leme et al (2004) y los términos morfológicos utilizados por Sinclair (1940Sinclair ( , 1942Sinclair ( , 1948Sinclair ( , 1952, Moore & Harrington (1956), Bischoff (1978), van Iten (1991a,b), van Iten et al (1996) y Leme et al (2004).…”
Section: Paleontología Sistemáticaunclassified